Kemampuan Kepala Sekolah dan Partisipasi Orang Tua dalam Meningkatkan Performa Guru di sekolah Dasar - Yuliana, Winditiya; Zainuddin, Zainuddin (Kelola: Jurnal Manajemen Pendidikan, 2024)
The principal's job is to mobilize people in the school organization so they can work optimally. The community and parents can collaborate to provide ideas for assistance and become resource persons in various activities to improve the quality of education in schools. The aim of this research is the ability of school principals and parent participation in improving teacher performance in elementary schools. The method used in this research is explanatory research, with the sampling technique being a Regional Sample (Probability Sample Area), meaning that the sampling technique is carried out by taking representatives from each region contained in the population. The respondents in this study were 25 people. The instrument test analysis method used in this study includes validity and reliability tests. The research results show that the teacher's duties will run well if they are supported by good communication from the school principal and the student's guardians. The motivation of a leader, in this case the principal, is essential and plays a role so that teachers and employees can synergize and carry out their duties with full responsibility and optimal results, namely good performance.